Implementing Universal Health Insurance: Case Study of Stakeholders' Perspectives in Port Said, Egypt - Hetta, Rana (AUC Knowledge Fountain, 2024)
This research delves into the multifaceted dimensions of healthcare access through the lens of stakeholders in Port Said, Egypt, following the implementation of Universal Health Insurance (UHI) policies. The central research question explores the impact of UHI policies on healthcare access in Port Said. A set of investigative questions guides this exploration, focusing on beneficiary experiences, healthcare staff perspectives, and the alignment of UHI system implementation with beneficiaries’ healthcare needs. This study seeks to comprehend the institutional and policy context of UHI in Egypt, providing insights from policymakers, healthcare workers, and beneficiaries. Port Said serves as a case study, given its status as the pioneering governorate in UHI implementation within Egypt. Framed around "accessibility," this research assesses how the implementation environment influences access experiences from the viewpoints of these stakeholders. This research generates stakeholder-informed policy recommendations for the continued expansion of the UHI system and contributes to the broader literature on Universal Health Coverage (UHC) and healthcare access in Low- and Middle-Income Countries (LMICs), offering a unique framework rooted in stakeholders' perspectives. The research findings underscore several key recommendations including restructuring incentives to encourage private sector and community-based provider participation is crucial for expanding service availability. Secondly, a revision of enrolment criteria and channels is warranted to ensure inclusivity. Lastly, the introduction of independent performance monitoring mechanisms is recommended to enhance accountability and performance within the UHI system.